Structural and semantic features of proper names of Kazakhs and Tuvans - Tuimebayev, Zhanseit K.; Kikbayeva, Ainur T.; Suvandii, Nadezhda D. (The New Research of Tuva, 2025)
The article examines personal names of the Kazakhs and Tuvans, analyzing their semantic-lexical parallels and morphological features. Common elements in the structure and semantics of personal names are identified. This comparative study is motivated by an interest in the naming systems of two genetically related Turkic languages, which developed under a shared linguistic situation in the 20th century, shaped by contact with the Russian language.The sources used include collections of names compiled and published by Kazakh and Tuvan researchers in various editions.As a result of the conducted analysis, 16 common models of name derivation and 13 semantic groups of personal names were identified. Among the revealed lexical-semantic groups, particular attention is given to personal names derived from names of domestic and wild animals, and items of national and everyday life that reflect the specifics of the nomadic lifestyle and economic activities of the Tuvan and Kazakh peoples. Instances of name changes influenced by the Russian language and Soviet culture are also noted.
Keywords: anthroponymy; Kazakh language; Tuvan language; bilingualism; lexical-semantic parallel; proper name